Managing Coal Mine Closure : Achieving a Just Transition for All - World Bank Group (World Bank, Washington, DC, 2018)
Over the last half century, large-scale changes to coal industries across Europe, and more recently in the United States and China, have resulted in as many as 4 million coal workers losing their jobs. The main drivers of these changes are mine mechanization, government policies and competition from other fuels in downstream energy demand markets. At present, economies in Asia, Eastern Europe, and Africa face these same drivers of change, with large job losses already taking place in China, and with other large coal producing countries in Asia likely to follow. Lessons drawn from the experiences of the Russian Federation (Russia), Ukraine, Poland, and Romania from 1994 to 2012, complemented by data on impacts of coal industry adjustment in the United Kingdom, the Netherlands, the United States, and China, show that job losses not only take place as the industry contracts but even if production is increasing. The mitigation of social conflict and economic distress are of grave concern as globally the coal industry enters a new era of downsizing. The objective of this report is to share with governments lessons learned regardingcoal mine closure. Indeed, the full set of coal mine closure issues is diverse with few positive case studies to date to draw on. The complexity of technical issues and vested interests along with the myriad of potential risks which may unfold will require combining time-tested and new approaches, and applying a broad array of skills. In this issues paper, we have sought to identifylessons from the past that can guide policy makers for more successful future mine closures. Nine lessons learned are presented for government consideration, drawn from three sets of literature. First, analysis from coal industry adjustment and downsizing experiences in Russia, Ukraine, Poland, and Romania from 1994 to 2012 where interventions ranged from preparatory diagnosticand technical studies to planning and financing of eventual closure programs. Second, observations and insights on impacts from coal industry adjustment in the United Kingdom, the Netherlands, the United States, and China. Third, evidence-based interventions that have helped to mitigate potential negative social and labor impacts from mass job losses in other industries.